2015
DOI: 10.1177/1040638715585865
|View full text |Cite
|
Sign up to set email alerts
|

PRNP variants in goats reduce sensitivity of detection of PrPSc by immunoassay

Abstract: Abstract. Diagnostic analyses often employ single antibody systems but are potentially limited by epitope sequence variation. United States regulatory testing for scrapie primarily uses antibody F99/97.6.1 for immunohistochemistry (IHC) of the prion protein associated with scrapie (PrP Sc ). Whereas the epitope bound by F99/97.6.1 is highly conserved in sheep, a polymorphism in caprine PRNP results in a glutamine to lysine change at codon 222 and affects PrP detection. This study evaluated the performance of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
(89 reference statements)
2
17
0
Order By: Relevance
“…In addition, the performance of these tests for the identification of atypical scrapie and BSE in sheep was also evaluated. [10][11][12][13][14][15][16][17][18][19] Only IDEXX, a Bio-Rad SAP, b and Bio-Rad SG c rapid tests (enzyme-linked immunosorbent assays [ELISAs]) were able to detect atypical scrapie, a result also confirmed by routine screening for scrapie in sheep and goats. 3,22 In 2012, the European Food Safety Authority also recommended the PrioSTRIP SR d test (visual reading protocol) for the detection of TSE disease in small ruminants.…”
mentioning
confidence: 99%
“…In addition, the performance of these tests for the identification of atypical scrapie and BSE in sheep was also evaluated. [10][11][12][13][14][15][16][17][18][19] Only IDEXX, a Bio-Rad SAP, b and Bio-Rad SG c rapid tests (enzyme-linked immunosorbent assays [ELISAs]) were able to detect atypical scrapie, a result also confirmed by routine screening for scrapie in sheep and goats. 3,22 In 2012, the European Food Safety Authority also recommended the PrioSTRIP SR d test (visual reading protocol) for the detection of TSE disease in small ruminants.…”
mentioning
confidence: 99%
“…The donor goats were closely monitored for clinical signs of scrapie and subsequently euthanized by venous administration of a commercially available barbiturate solution. Postmortem tissues were fixed in formalin and processed for assessment of PrP Sc accumulation by scrapie IHC (described below) [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, identification of scrapie status of goats can be complicated due to the existence of several polymorphisms in the PRNP coding sequence which can delay the scrapie incubation period and PrP Sc accumulation (Dassanayake et al, 2015;Goldmann et al, 2011;Lacroux et al, 2014). A recent study by us revealed that the polymorphisms in caprine PRNP can also affect the sensitivity of PrP Sc detection in brain samples by anti-prion mAb-based immunoassays such as IHC and Western blot analysis (Madsen-Bouterse et al, 2015). It therefore becomes important to have a rapid, sensitive, PRNP polymorphism-independent as well as antibody-independent detection test to detect scrapie.…”
Section: Discussionmentioning
confidence: 99%
“…Scrapie-uninfected donor goats (n53) were born and housed in a scrapie-free farm at Washington State University with no direct contact with scrapie-infected animals. Of the scrapie-infected donor goats, those bearing WT prion gene (PRNP) haplotypes (n53) were born and raised by scrapie-infected does at the scrapie quarantine farm of the US Department of Agriculture (USDA) Animal Disease Research Unit (Pullman, WA, USA), whereas those heterozygous PRNP with a minor allele (n53) had been referred to us by the USDA Animal and Plant Health Inspection Service (Madsen-Bouterse et al, 2015;O'Rourke et al, 2012). The PRNP genotypes of goats were determined by sequencing the ORF of PRNP as described previously (White et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation